THE CULTURE OF POTTERY IN ZANZIBAR (مجلة العلوم الشاملة, 2026)
Zanzibar is an archipelago globally recognized for its rich culture, which has emerged from the confluence of diverse communities. These communities, including Indians, Arabs, and mainland Africans, arrived in the Zanzibar islands and blended with the indigenous inhabitants. From this interaction arose generations who cultivated Zanzibari culture through various art forms, such as carving, weaving, painting, and pottery.The pottery art of Zanzibar is a tradition that has endured and is highly cherished by many of the island's communities. Indeed, any discussion of this art form in Zanzibar necessarily centers on the village of Fumba in the West Region of Unguja Island. Fumba is celebrated from antiquity as the birthplace of pottery, historically known as the home of the famed late potter and singer, Siti binti Saadi. Her initial recognition came from selling pots in town while singing, her captivating voice drawing crowds who urged her to become a performer (Robert, 1976).The art of pottery involves the creation of various household utensils using clay as the primary raw material. These items include cooking pots (*vyungu*), large pots (*vikaango*), water jars (*mikungu*), incense burners (*vyetezo*), small bowls (*vibia*), water storage vessels (*magudulia*), pitchers (*mitungi*), coconut graters (*mikungu ya kukunia nazi*), and various decorative objects produced on different scales.While a superficial examination might suggest that pottery is being rendered obsolete by scientific and technological progress, a closer look reveals that, in other respects, the art form continues to develop in various ways. Pottery is being innovated and crafted in new styles, providing aesthetic pleasure to observers. Modern and veteran potters alike continue to demonstrate their evolving skills, crafting this art with a mastery that astonishes viewers through the unique character of their vessels.